Agents of Change or Control? Correlates of Positive and Negative Staff-inmate Relationships among a Sample of Formerly Incarcerated Inmates. Issue 3 (27th May 2022) - Logan, Matthew W.; Jonson, Cheryl Lero; Johnson, Shelley; Cullen, Francis T.
ABSTRACT: Prior studies of staff-inmate interactions suggest that they are primarily adversarial in nature. However, less is known about the key factors that influence inmate-staff relationships. Using a sample of formerly incarcerated males in the state of Ohio, the impact of various demographic and institutional characteristics on positive and negative perceptions of correctional staff (by inmates) are assessed. Specifically, ordinary least squares (OLS) regression is employed to examine the variation in perceptions that is accounted for by measures of the inmates' social, demographic, and criminal histories (i.e., imported characteristics) as well as the characteristics of the facilities in which they are housed (i.e., deprivation measures). Individual characteristics exert significant effects on inmate perceptions of staff, whereby (1) younger inmates, (2) minority inmates, (3) inmates with higher levels of education, and (4) inmates with more extensive criminal histories were more likely to hold more negative views of correctional staff. Institutional characteristics also significantly influence inmate perceptions of staff, whereby inmates who have (1) experienced victimization, (2) received less social support, and (3) participated in treatment programs were more likely to hold more negative views of correctional staff. Findings suggest that staff can serve as either agents of change or control for inmates.